'Carriers of V‐LH among 1593 Baltic men have significantly higher serum LH'. (26th March 2015) - Punab, A. M.; Grigorova, M.; Punab, M.; Adler, M.; Kuura, T.; Poolamets, O.; Vihljajev, V.; Žilaitienė, B.; Erenpreiss, J.; Matulevičius, V.; Laan, M.
Summary: Luteinizing hormone (LH) is a pituitary heterodimeric glycoprotein essential in male and female reproduction. Its functional polymorphic variant (V‐LH) is determined by two missense mutations (rs1800447, A/G, Trp8Arg; rs34349826, A/G, Ile15Thr) in the LH β‐subunit encoding gene ( LHB ; 19q13.3; 1111 bp; 3 exons). Among women, V‐LH has been associated with higher circulating LH and reduced fertility, but the knowledge of its effect on male reproductive parameters has been inconclusive. The objective of this study was to assess the effect of V‐LH on hormonal, seminal and testicular parameters in the Baltic young men cohort ( n = 986; age: 20.1 ± 2.1 years) and Estonian idiopathic infertility patients ( n = 607; 35.1 ± 5.9 years). V‐LH was detected by genotyping of the underlying DNA polymorphisms using PCR‐RFLP combined with resequencing of a random subset of subjects. Genetic associations were tested using linear regression under additive model and results were combined in meta‐analysis. No significant difference was detected between young men and infertility patients for the V‐LH allele frequency (11.0 vs. 9.3%, respectively). V‐LH was associated with higher serum LH in both, the young men cohort ( p = 0.022, allelic effect = 0.26 IU/L) and the idiopathic infertility group ( p = 0.008, effect = 0.59 IU/L). In meta‐analysis, the statistical significance was enhanced ( p = 0.0007, resistant to Bonferroni correction for multiple testing; effect = 0.33 IU/L). The detected significant association of V‐LH with increased serum LH remained unchanged after additional adjustment for the SNPs previously demonstrated to affect LH levels ( FSHB ‐211G/T, FSHR Asn680Ser, FSHR ‐29A/G). Additionally, a suggestive trend for association with reduced testicular volume was observed among young men, and with lower serum FSH among infertility patients. The V‐LH carrier status did not affect sperm parameters and other circulating reproductive hormones. For the first time, we show a conclusive contribution of V‐LH to the natural variance in male serum LH levels. Its downstream clinical consequences are still to be learned.